Epidemiološke značilnosti kožnega malignega melanoma v Sloveniji - Pompe-Kirn, Vera (Radiology and oncology (Ljubljana), 1999)
Since the year 1980, also in Slovenia the incidence in skin malignant melanomahas been steeply increasing. In the period 1994-1996 an average numberof 82 new cases in men and 93 cases in women was registered. The prediction for th eperiood 2005-2009 has been 147 cases in men and 93 cases in women. In Slovenia, an unfavorably high percentage of advanced (Clark IV and V) stage at diagnosis was registered. Th e most frequently site of skin lesions was trunk (51%) in men, and lower limb (39%) in women. In the period 1973-1993 the five-, and ten-year patient's survival with invasive disease wasgradually improving. For the patients diagnosed in 1991-1993 the observed survival in men was 50,5%, and the relative survival 58,8%, while in women these rates were 62,5% and 68,2% respectively. In patients with a localized tumor the observed survival was 60% and the relative survival 69% in men, while in women the relevant rates were 71% and 76,5%, respectively. It is due to the high percentage of the advanced stages that Slovenia ranked the second-last for men, and the third-last for women, amongst 45 registries from 17 selected, mainly more developed countries.
Keywords: epidemiologija; Epidemiology; Incidence; kožne bolezni; Melanoma; rak (medicina); Skin neoplasms; Slovenija; Survival rate